The Ion Formation and Quantitative Response of Isoprene, Monoterpenes and Terpenoids in Ion Mobility Spectrometry with Atmospheric-Pressure Chemical Ionization as a Function of Temperature - Thomas Mayer; Ralf Petrich; Helko Borsdorf (Sensors)
Ion mobility spectrometry is successfully used as a sensor technology for different applications. A feature of this method is that characteristic ion mobility spectra are obtained for each measurement rather than a sum signal. The spectra result from the different drift velocities of ions in a drift tube at atmospheric pressure. In this study, we investigated the ion formation processes and the quantitative response of isoprene, monoterpenes and monoterpenoids as a function of the temperature of the spectrometer using a tritium ionization source. These substances are important target analytes in atmospheric monitoring and in the analysis of essential oils in different matrices. A drift tube temperature above 120 °C permitted the most sensitive detection of isoprene and monoterpenes, while 80 °C was sufficient for the sensitive detection of most terpenoids. Dimer ions were formed for isoprene over the whole temperature range. The ionization processes of monoterpenes and terpenoids were strongly influenced by the temperature. At temperatures of 40 °C, adduct ions were formed in addition to MH+ ions for monoterpenes. Enhanced temperatures provided a single peak with the same drift time for all monoterpenes. Structural differences influenced the ion formation of terpenoids, and much more complex spectra were obtained. The nature of the product ions changed depending on the temperature.